(3TQM GdSde GdeQhfb aj GdefWbs - (3GdCNVQj, YHO GdQMef Hf eMeO Hf eMeO J (B983 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd bdhH GdYdeGA SehGJ JJLdG ajgG TehS GdeYGQa hHYO adeG hVYJ GdCQLhRI GdeSeGI HGdSde GdeQhfb Ydi GdefWb Ydi Cf CVY YdjgG TQMG GdMeO ddg GdPj bO CNQLG bGd GdeMbbs
(3BNQgG (B:s
(3dGJHGY GdbOS hVYJg aj GdChbGJ GdeGjdI GdJj dgG YQV hCeG GdbeQ ajbe aj cd HQL djdJjf hKdGKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 331s
(3eYLe GdeDdajf (B2 / 119s
(3cTa GdXfhf (B2 / 998s
(3gOjI GdYGQajf (B6/ 546s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs